Nature of active vanadium nanospecies in MCM-41 type catalysts for olefins oxidation - Chanquia, Corina Mercedes (2016)
A multi-technique physicochemical investigation including UV–Vis-DRS, Raman spectroscopy, XPS, ESR and FTIRS with pyridine adsorption was performed to analyze the nature of different vanadium nanospecies present on MCM-41 type catalysts. By employing a direct hydrothermal synthesis, vanadium species were incorporated into siliceous structure mainly as tetrahedrally coordinated isolated Vδ+ ions, which would be located inside the wall and on the wall surface of the mesoporous channels. The coexistence of both vanadium oxidation states V4+ and V5+ was also revealed. Acidity measurements permitted to infer about the majority presence of Lewis acid sites, which increase with vanadium content. The catalytic performance of these materials was evaluated in the reaction of α-pinene oxidation with H2O2. The highest intrinsic activity of the sample with lower V loading was attributed to the high dispersion and efficiency of the isolated Vδ+ species that actuate as active sites. A mixture of reaction products arising from competitive processes of epoxidation and allylic oxidation was found.